In vivo CEST MR imaging of U87 mice brain tumor angiogenesis using targeted LipoCEST contrast agent at 7 T. Issue 1 (29th February 2012) - Flament, Julien; Geffroy, Françoise; Medina, Christelle; Robic, Caroline; Mayer, Jean‐François; Mériaux, Sébastien; Valette, Julien; Robert, Philippe; Port, Marc; Le Bihan, Denis; Lethimonnier, Franck; Boumezbeur, Fawzi
Abstract LipoCEST are liposome‐encapsulating paramagnetic contrast agents (CA) based on chemical exchange saturation transfer with applications in biomolecular MRI. Their attractive features include biocompatibility, subnanomolar sensitivity, and amenability to functionalization for targeting biomarkers. We demonstrate MR imaging using a targeted lipoCEST, injected intravenously. A lipoCEST carrying Tm(III)‐complexes was conjugated to RGD tripeptide (RGD‐lipoCEST), to target integrin ανβ3 receptors involved in tumor angiogenesis and was compared with an unconjugated lipoCEST. Brain tumors were induced in athymic nude mice by intracerebral injection of U87MG cells and were imaged at 7 T after intravenous injection of either of the two contrast agents (n = 12 for each group). Chemical exchange saturation transfer‐MSME sequence was applied over 2 h with an average acquisition time interval of 13.5 min. The chemical exchange saturation transfer signal was ∼1% in the tumor and controlateral regions, and decreased to ∼0.3% after 2 h; while RGD‐lipoCEST signal was ∼1.4% in the tumor region and persisted for up to 2 h. Immunohistochemical staining revealed a persistent colocalization of RGD‐lipoCEST with ανβ3 receptors in the tumor region. These results constitute an encouraging step toward in vivo MRI imaging of tumor angiogenesis using intravenously injected lipoCEST. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.